Determination of Uranium, Thorium and Potassium for Optically Stimulated Luminescence Dating by ICP-MS and XRF - Na WANG; Lei WU; Jiasong WANG; Yang YU; Jiangping ZENG; Yongsheng CHEN; Fu WANG (Yankuang ceshi)
Optically stimulated luminescence (OSL) dating includes the measurement of the equivalent dose and the environmental dose rate. The accurate determination of uranium, thorium and potassium is an important step in ensuring the accurate calculation of the environmental dose rate. The commonly used measurement method is the combination of inductively coupled plasma-mass spectrometry/optical emission spectroscopy (ICP-MS/OES), but the determination of uranium, thorium and potassium can not be done at the same time, and the measurement time is long. In the research, two methods of ICP-MS and X-ray fluorescence spectrometry (XRF) measuring the three elements were compared. Using ICP-MS analysis, electronic dilution was used to reduce the potassium ions entering the detector, so that potassium ions were in the same order of magnitude as uranium and thorium ions. Thus, the simultaneous analysis of high content potassium and low content uranium and thorium was achieved. The detection limits for uranium, thorium, and potassium were 6.38ng/L, 8.52ng/L, and 926ng/L, respectively. The effects of closed acid dissolution method and open acid dissolution method on the determination of uranium, thorium, and potassium by ICP-MS method were studied. The two dissolution methods dissolved 10 sediment and soil standard substances, and the results of uranium, thorium, and potassium determination were accurate and reliable, with no significant difference in relative error, ranging from 0 to 9.33%. However, the operation of open acid dissolution method was simpler, and the sample processing time (about 9h) was much shorter than the closed acid dissolution method (about 60h). Therefore, open acid dissolution was selected to dissolve the sample in ICP-MS method. By XRF analysis, the relative errors for the determination of uranium, thorium and potassium in standard materials by pressed-powder pellets method were 4.78%−16.2%, 1.20%−13.3% and 0.00%−5.67%, respectively. ICP-MS and XRF were used to determine 20 sediment samples from Bohai Bay, and the relative deviation of the environmental dose rate was less than 6%. XRF has advantages in the measurement of potassium and is more suitable for luminescent samples with high potassium content. The ICP-MS method has a lower detection limit, and higher precision and accuracy for the determination of uranium and thorium. For ultra trace samples, this method provides more accurate measurement results.